Dancing with care: promoting social integration and participation in community activities for older adults - An, Jianzeng; Xia, Chun; Xu, Jia; Li, Weiwei; Ding, Jianwen (Frontiers in Public Health, 2024)
BackgroundIt is common for older adults to move to urban communities after retirement, living with their adult children and caring for grandchildren in China. This impacts their social networks and, consequently, their psychological and physical health. However, research on proactive ways to mitigate the negative effects of social dislocation is lacking. This study examined how dancing with care (DWC), a new form of preventative care, promotes social integration among older adults in Chinese communities, focusing specifically on participants’ experiences related to community engagement, mutual support, volunteer activity, social connections, and advanced learning through their involvement with DWC.MethodsSemi-structured interviews were conducted with 60 older adults who regularly participated in DWC in communities in southern China.ResultsDWC’s dimensions play a vital role in addressing the social integration of older adults. Through DWC, older adults participate in community activities, engage in mutual support, volunteer in various activities, develop social connections, and learn different things, including the use of advanced technologies.ConclusionDWC addresses older people’s social integration by providing opportunities to be involved in the community. It provides a promising path for older adults to actively engage in the revival of social capital within their social networks in the community. This study offers valuable insights for enhancing social involvement for older adults.